2004
DOI: 10.21273/hortsci.39.5.1138
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Tolerance of Seashore Paspalum Ecotypes: Shoot Growth Responses and Criteria

Abstract: Evaluation of turfgrass salt tolerance is a basic strategy for selecting grasses that can be grown in areas with salt-affected water or soils. Our objectives were to determine the relative salinity tolerances of 32 grasses and to evaluate potential shoot-based criteria for assessing salinity tolerance. Shoot growth responses to salinity of 28 seashore paspalums (Paspalum vaginatum Swartz) and four bermudagrass [Cynodon dactylon (L.) × C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 22 publications
5
39
2
Order By: Relevance
“…The objectives of the present study were to examine genotypic variations in salt tolerance in seashore paspalum, to characterize physiological effects of choline on salt tolerance, and to determine how GB and major lipids (glycolipids and phospholipids) affected by choline may be involved in choline regulation of salt tolerance. The two genotypes, Adalayd and Sea Isle 2000, were selected to represent genotypic variations in salt tolerance in this study based on our preliminary genotype screening of five genotypes (Adalayd, Excalibur, Temple2, Sea spray, and Sea Isle 2000), and previous reports by others, which reported that Adalayd was relatively more salt sensitive and Sea Isle 2000 was salt tolerant (Lee, Carrow, & Duncan, ; Lee, Carrow, & Duncan, ; Lee, Duncan, & Carrow, ). SeaIsle 2000 was selected as a mutation derived from the parental cultivar Adalayd (Duncan, ) and was specifically developed for high salt tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of the present study were to examine genotypic variations in salt tolerance in seashore paspalum, to characterize physiological effects of choline on salt tolerance, and to determine how GB and major lipids (glycolipids and phospholipids) affected by choline may be involved in choline regulation of salt tolerance. The two genotypes, Adalayd and Sea Isle 2000, were selected to represent genotypic variations in salt tolerance in this study based on our preliminary genotype screening of five genotypes (Adalayd, Excalibur, Temple2, Sea spray, and Sea Isle 2000), and previous reports by others, which reported that Adalayd was relatively more salt sensitive and Sea Isle 2000 was salt tolerant (Lee, Carrow, & Duncan, ; Lee, Carrow, & Duncan, ; Lee, Duncan, & Carrow, ). SeaIsle 2000 was selected as a mutation derived from the parental cultivar Adalayd (Duncan, ) and was specifically developed for high salt tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Significant variation in salt tolerance exists in seashore paspalum accessions (Lee et al, 2004). Lee et al (2008) demonstrated that nine salt tolerant and sensitive genotypes all accumulate proline and Glycine betaine with increasing salt concentrations which suggests that seashore paspalum uses osmotic adjustment in response to added salt concentrations.…”
mentioning
confidence: 99%
“…This grass species is highly salt tolerant [22] and was considered as an ideal candidate plant species for vegetative cover establishment in red mud disposal sites. Stolon segments (ca.…”
Section: The Test Plantmentioning
confidence: 99%